2021
DOI: 10.1021/acsomega.0c05371
|View full text |Cite
|
Sign up to set email alerts
|

Sonocogreen Decoration of Clinoptilolite by CaO Nanorods as Ecofriendly Catalysts in the Transesterification of Castor Oil into Biodiesel; Response Surface Studies

Abstract: A CaO/clinoptilolite green nanocomposite (CaO/ Clino) was synthesized by a green modification technique using calcium nitrate and green tea extract. The CaO/Clino nanocomposite promises a total basicity of 4.82 mmol OH/g, surface area of 252.4 m 2 /g, and ion exchange capacity of 134.3 mequiv/ 100 g, which qualifies the product as an effective catalyst in the transesterification of castor oil. The transesterification performance of the CaO/Clino catalyst was addressed statistically based on the response surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Each plot described the effects and interaction of two variables with the third variable fixed at the medium level. Different shapes of the plots indicated various interactions between two variables [80]. Fig.…”
Section: Optimization Of Specific Surface Area By Rsmmentioning
confidence: 96%
“…Each plot described the effects and interaction of two variables with the third variable fixed at the medium level. Different shapes of the plots indicated various interactions between two variables [80]. Fig.…”
Section: Optimization Of Specific Surface Area By Rsmmentioning
confidence: 96%
“…Natural minerals have advantages, such as thermal and chemical stability, common availability, large specific surface area, low cost, and nontoxicity . The structure of vermiculite (VMT) can be broken down into tetrahedral sheets of oxygen and coordinated octahedral sheets of aluminum or iron oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 24 developed Ni−Co−P hollow nanobricks, with high sensitivity (∼3.6 kΩ/ % RH), low hysteresis (∼3% RH), good repeatability in a wide moisture range from 0 to 97.5% RH, and a response (recovery) time of 95 s (27 s). Natural minerals have advantages, such as thermal and chemical stability, 25 common availability, 26 large specific surface area, low cost, and nontoxicity. 27 The structure of vermiculite (VMT) can be broken down into tetrahedral sheets of oxygen and coordinated octahedral sheets of aluminum or iron oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium oxide (CaO) has been widely considered as the efficient transesterification catalyst of vegetable oils due to its low cost and easy commercial availability with high international reserves as well as high basicity, high safety, and low alcohol solubility. , It has been postulated that the oxygen anion presented on the CaO surface that possesses basic properties initiates the base-catalyzed reaction by abstracting a proton from alcohol as well as by the interaction between a Lewis basic site (oxygen anion) and reactants (esters); these double activated intermediates could thus facilitate undergoing transesterification . We also recently reported that CaO catalyzed high yield synthesis of FAEs by transesterification of soybean, rice bran, and palm oils with ethanol at 150–200 °C .…”
Section: Introductionmentioning
confidence: 99%